Interpretasi Hadis Kesaksian Tunggal Perempuan: Implementasi Pada Korban Pelecehan Seksual - Dzulkifli Al-Amin; Zulfahmi Alwi; Andi Darussalam (Journal on Education, 2024)
Hadith as a source of Islamic teachings is permitted to apply in responding contemporary issues such as sexual violence in which women are generally victimized. Cultural and social values or religious understandings often put women in the secondary position including being witness. Female witness should be two people compared to their male counterparts which are one. There is no room for them to have equal number with men, but hadith is clearly stated that women can be a primary witness which was initially occurred in the breastfeeding case. It is, therefore, the significant question is that why this hadith cannot be applied in sexual violence against women due to the facts that these are serious problems both in the global world and Indonesia. This research is qualitative using textual, intertexts and even contextual analysis in understanding the hadith and connecting to social and cultural context of sexual violence against women. The research shows that although there are clear qur’anic messages with respect to men and women of being witness (Q.S. Al-Baqarah: 282), woman can become a primary witness based on this hadith. The inclusive hadith is not contradictory with the qur’anic message because the conditions are different.